2015
DOI: 10.1007/s11085-015-9538-3
|View full text |Cite
|
Sign up to set email alerts
|

The Oxide Scales Formed on a Dispersion-Strengthened Powder Metallurgical FeCrAl Alloy at 900 °C in O2 and in O2 + H2O

Abstract: Early oxide scale growth on an oxide dispersion strengthened rapidly solidified powder FeCrAl material, Kanthal Ò APMT, was investigated at 900°C in an O 2 ? N 2 and an O 2 ? H 2 O ? N 2 environment for up to 168 h. Gravimetry was used to follow oxide growth and the oxide scale was examined with XRD. Scale morphology was investigated in detail with SEM/EDX, TEM/EDX/CBED. The alloy rapidly formed a protective two-layered a-alumina scale containing oxide nodules. Between the top and bottom alumina layers there w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…1). A TEM investigation by Hellström et al confirmed the presence of a two-layered a-Al 2 O 3 scale after oxidation at 900°C, the inward growing alumina layer was however not continuous over the entire surface [18]. Analysis using XRD showed that a-Al 2 O 3 was present on all pre-oxidized samples.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…1). A TEM investigation by Hellström et al confirmed the presence of a two-layered a-Al 2 O 3 scale after oxidation at 900°C, the inward growing alumina layer was however not continuous over the entire surface [18]. Analysis using XRD showed that a-Al 2 O 3 was present on all pre-oxidized samples.…”
Section: Resultsmentioning
confidence: 97%
“…95 % N 2 . The chosen pre-oxidation conditions were studied more in detail by Hellström et al [18,19]. A short description of the obtained alumina scales can be found below.…”
Section: Resultsmentioning
confidence: 99%
“…Materials used for boilers and heat exchangers in coal‐fired power plants suffer from fireside corrosion, a mechanism proposed to be caused by the accumulation of molten salts . The propagation mechanism of fireside corrosion was shown recently by Lutz et al to be analogous to hot corrosion Type II. Hot corrosion has often been investigated on nickel‐ and cobalt‐based alloys for turbine engine applications where Na 2 SO 4 deposits from the combustion environment result in accelerated failure.…”
Section: Introductionmentioning
confidence: 99%
“…As the steam temperatures in coal‐fired power plants are increased to achieve higher efficiencies, the surface temperatures of the boiler and heat exchanger increase towards 700°C . The temperature dependency of hot corrosion Type II on both nickel‐ and iron‐based alloys is generally assumed to follow a bell‐shaped curve and the maximum metal loss is typically observed in the regime around 700°C but can be offset by SO 2 , the alkali content or the alloy composition . As the increasing temperatures reach the regime of maximum metal loss, the investigation of commercial alloys and their resistance against hot corrosion Type II remains an ongoing topic …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation